HPLC fucoxanthin profiles of a microalga, a macroalga and a pure fucoxanthin standard - Foo, Su Chern; Md.Yusoff, Fatimah; Ismail, Maznah; Basri, Mahiran; Yau, Sook Kun; Khong, Nicholas Mun Hoe; Chan, Kim Wei; Ebrahimi, Mahdi (Elsevier, 2017)
Data in this article illustrate representative fucoxanthin chromatograms of a microalga, Chaetoceros calcitrans; a macroalga, Saccharina japonica and; a pure fucoxanthin standard. High performance liquid chromatography (HPLC) eluted fucoxanthin at the 7.008±0.024th min. This data article refers to the research article ‘‘Antioxidant capacities of fucoxanthin-producing algae as influenced by their carotenoid and phenolic contents’’ Foo et al. [1]; where a more comprehensive data interpretation and analysis is explained.